Marketing patterns of agricultural commodities in an upland area of Central Java - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1986)
ABSTRACT In the uplands of Central Java a wide variety of dry cultivated crops are produced for subsistence as well as for cash. The marketing channels for these crops are also diverse. The producers can choose between selling at the market place or at their farms